ANALISIS KINERJA KEUANGAN PADA CV NABIL SUKSES MANDIRI TEGAL - Slamet Nasroni (Jurnal Strategik, 2017)
ABSTRACT The purpose of the research is to analyze financial performance on CV Nabil Sukses Mandiri Tegak through activity ratio analysis and profitability ratios. The research model conducted is through field research (field research), namely research directly in the company by conducting direct interviews with leaders and employees of the company and library research, namely research conducted using literature and writing - writings that are closely related to the object of writing intended to obtain a theoretical basis will be used in discussing the problem under study. The results showed that the ratio of activities which included receivable turnover, inventory turnover, and total asset turnover had increased even though the total asset turnover in 2015 had decreased slightly by 1.29 to 2.28 times. While the profitability ratio which includes gross profit margin, net profit margin and return on investment has increased from 2012 to 2016.